Secrets of the profession of professional accountants - Akmal Yorievich Ostanov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the accounting profession is considered as a specialist who knows his work, has various personal and professional qualities, and thinks about the secrets of his profession.